Multi-stimuli-responsive materials with optical modulation for smart windows - Pang, Yong Kai (Nanyang Technological University, 2021)
Energy consumption is increasing rapidly with higher world population, income and access to electricity. Windows are widely found in buildings and considered to be the most inefficient part which can be further modified in order to save energy. Hence, smart windows are introduced which can control light transmittance and solar radiation, reducing energy consumption significantly. In this report, multi-stimuli responsive films were produced that have great potential for smart window application. The flim consist of a silica (SiO2) layer which contains closed-packed SiO2 nanoparticles where this layer is then embedded inside elastomeric polydimethylsiloxane (PDMS) at the bottom layer and vanadium dioxide (VO2) nanoparticles embedded inside PDMS is found at the top layer, forming a SiO2/VO2/PDMS composite film, where VO2 gives the near infrared modulation via heat stimulous, while SiO2 patterning gives luminous transmission modulation via stretching. In the SiO2/VO2/PDMS composite film, it has a Tlum of 49.98% at 20ºC. After heating to 100ºC, the film has a Tlum of 50.49% and ΔTsol of 10.32%. With elongation at 100ºC, the film has a Tlum of 22.98% and ΔTsol of 27.76%. Dual stimulus controls overcoming the intrinsic limitation of VO2 and can largely increase the solar modulation. We can conclude that both incorporation of SiO2 and VO2 nanoparticles in the composite film leads to optical modulation through its individual mechanism.